Croatian translators' take on Swedish collocations and idioms - Antunović, Goranka (Array, 2006)
cjelokupni tekst: Abstract: From the translator's point of view, collocations and idioms belong to rather demanding text units, which often require a high level of linguistic, communicative, cultural and translational competence. The translator needs to be aware, and appreciative of their semantics (the difficulty with idioms being that their meaning is not deducible from that of the individual elements), their syntax (non-free and sometimes puzzling), their pragmatics (related to a variety of linguistic and textual circumstances, more specific of which can stem from conscious breach of the frozen syntax, the metaphorical quality of their meaning or culture-specific usage patterns) on both the source and the target end of the translation process. In addition, a successful choice of an appropriate equivalent requires a well-founded translational decision as to the most relevant aspect(s) of the value of the phrase in question i.e. the aspect which should be matched in the translation, as well as an awareness of the various procedures that can be employed. The paper discusses translation equivalents of Swedish collocations and idioms manifest in Croatian translations of about 1000 book pages of Swedish fiction. In an attempt to check whether there are any patterns in the treatment of collocations and idioms in translation, the discussion focuses on the following characteristics of the established equivalents: - whether they are the same type of linguistic units as the original phrase (collocation or idiom) ; - which aspect of the original phrase’ s linguistic and communicative value has been given prominence in the translation (i.e. is best matched by the chosen translation equivalent) ; - whether they can be considered lexical or grammatical calques (if yes, of what kind). The basis for the discussion is provided by twofold procedure: - a systematic analysis of all the translation equivalents of ten Swedish lexical collocations / idioms established in the translation of seven books of fiction ; - an analysis of the equivalents of some other lexical collocations and idioms established in randomly selected extracts from three other novels. The analysis is primarily expected to offer an insight into the ways in which lexical collocations and idioms are commonly perceived and treated. In addition it will feed into a more general picture of translation practices and translation norms in Croatia.